Malaysia island development at the Marine Park: Impact to the coral reef - Sazali, Muhamad Ferdhaus; Azlan, Mohd Rezza Petra; Mohamed, Badaruddin (2013)
Island tourism is one of the fastest growth sectors in Malaysia. Islands in Malaysia are famous around the globe with its beautiful nature, culture and sparkling blue seawater. Malaysia boasts some of the most beautiful islands. An amazing number of these natural treasures lay nestled in tranquil bays and coves. Beneath the aquamarine waters lies a fascinating world of coral and marine life waiting to be discovered. Island development in Malaysia started to be developing tremendously due to the high number of tourist arrival to the island. Many hotel, resort and chalet had been built by the investor and the government agencies. Natural areas were explored when tourism development had been carried out. These physical developments come with tourism activities which led to the some impacts and challenges to the coral reef. The main objective of this paper is to examine the environmental impact of island development in Malaysia focus on the coral reef and to find which activities of development affecting coral communities. This preliminary study had been conducted by collecting all the possible secondary data from various sources like Department of Marine Park, Department of Survey and Mapping Malaysia (JUPEM) and Ministry of Tourism Malaysia. This pilot study is crucial for first step of conservation action and can benefits all parties in tourism sector, from hosts to tourists, authority body, researchers and many more.